The essential role of carefully optimized synthesis for elucidating intrinsic material properties of (Ga,Mn)As - Nĕmec, P; Novák, V; Tesařová, N; Rozkotová, E; Reichlová, H; Butkovičová, D; Trojánek, F; Olejník, K; Malý, P; Campion, R P; Gallagher, B L; Sinova, Jairo; et al. (Nature communications, 2013)
(Ga,Mn)As is at the forefront of spintronics research exploring the synergy of ferromagnetism with the physics and the technology of semiconductors. However, the electronic structure of this model spintronics material has been debated and the systematic and reproducible control of the basic micromagnetic parameters and semiconducting doping trends has not been established. Here we show that seemingly small departures from the individually optimized synthesis protocols yield non-systematic doping trends, extrinsic charge and moment compensation, and inhomogeneities that conceal intrinsic properties of (Ga,Mn)As. On the other hand, we demonstrate reproducible, well controlled and microscopically understood semiconducting doping trends and micromagnetic parameters in our series of carefully optimized epilayers. Hand-in-hand with the optimization of the material synthesis, we have developed experimental capabilities based on the magneto-optical pump-and-probe method that allowed us to simultaneously determine the magnetic anisotropy, Gilbert damping and spin stiffness constants from one consistent set of measured data.